A case report and literature review: one case of ceftriaxone sodium-induced reversible gallbladder stone - Luo, Changqin; He, Qingmin; Yang, Xiaocui (Frontiers in Medicine, 2024)
This paper reports a case of pseudolithiasis caused by the use of ceftriaxone sodium. The patient, a 54-year-old female, presented with intermittent abdominal pain and distension for one month. Initial ultrasonography showed no abnormalities. However, after receiving ceftriaxone sodium treatment for an upper respiratory tract infection, she developed discomfort in the right upper abdomen. A CT scan subsequently diagnosed her with gallbladder stones. Six weeks after discontinuing the medication, a follow-up examination revealed the disappearance of the stones, confirming the diagnosis of drug-induced pseudolithiasis. Through a literature review, this paper summarizes the mechanism, clinical manifestations, diagnostic methods, and treatment recommendations of ceftriaxone sodium-induced pseudolithiasis, providing a reference for clinical safe medication use.Ceftriaxone sodium, as a semi-synthetic third-generation injectable cephalosporin antibiotic, has been widely used in international clinical practice. Its unique antibacterial properties are exhibited by its high stability against the broad-spectrum β-lactamase produced by Gram-negative bacilli, especially showing significant antibacterial efficacy against Gram-negative bacilli such as Enterobacter.After being absorbed in the human body, this drug can penetrate tissues effectively and achieve wide distribution in the body. However, with its increasingly widespread clinical use, reports of related adverse drug reactions are also on the rise (1). This article thoroughly analyzes a case of pseudo-gallbladder stones caused by the injection of ceftriaxone sodium, and systematically summarizes the clinical manifestations, formation mechanism, and corresponding treatment measures of pseudo-stones induced by ceftriaxone sodium. It is hoped that this study can provide